Perceptions of well-being and physical performance in English elite youth footballers across a season - Noon, M. R.; James, R. S.; Clarke, N. D.; Akubat, I.; Thake, C. D. (Journal of Sports Sciences, 2015)
The 2011 English Elite Player Performance Plan (EPPP) stipulates training volumes that could put elite youth players at high risk of non-functional overreaching. The aim of the study was to assess player perceptions of well-being and physical performance to these high training loads. Fourteen academy football players (mean ± SD: age 17 ± 1 years; stature 179 ± 6 cm; body mass 70.8 ± 8.6 kg, at pre-season) completed a perception of well-being questionnaire 1-4 times per week throughout each training block (pre-season, in-season 1, 2, 3). Physical performance tests were carried out at the end of each training block. Increases in training exposure (P < 0.05; = 0.52) and moderate to large deteriorations in perceptions of well-being (motivation, sleep quality, recovery, appetite, fatigue, stress, muscle soreness P < 0.05; = 0.30-0.53) were evident as the season progressed. A moderate decrease in 30 m sprint performance (P < 0.05; = 0.48), a large improvement in Yo-Yo intermittent recovery test performance (P < 0.05; = 0.93) and small decreases in countermovement jump (P > 0.05; = 0.18) and arrowhead agility (P < 0.05; = 0.24) performance were evident as the season progressed. The present findings show an imbalance between stress and recovery in English elite youth players even when players experience lower training exposure than stipulated by the EPPP.